Composition and CEO Duality in Boards of Directors: An International Perspective - Dalton, Dan R.; Kesner, Idalene F. (Journal of International Business Studies, 1987)
This paper provides an empirical assessment comparing board composition (proportion of outside/nonmanagement board members) and CEO duality (role of CEO and chairperson held simultaneously) between samples (n=150) of Japanese, United Kingdom, and United States industrial firms. Results indicate marked differences in these corporate governance dimensions. Implications regarding board independence, and differences in corporate governance internationally are discussed.